Evaluasi Tingkat Keandalan Program Pemberdayaan Masyarakat Pendekar Dewa dalam Persepsi Penerima Manfaat - Isa Elfianto; Dyah Putri Utami; Karina Sindy Hapsari; Mohamad Adli; Esa Jati Manunggal Sukma Adhi; Mhd. Khadafi Ardika Panjaitan (Prosiding, 2026)
Corporate social responsibility programs oriented toward community empowerment require evaluation to ensure that their implementation is carried out consistently and aligns with the needs of beneficiaries. One important aspect that needs to be assessed is program reliability in delivering services, providing assistance, and implementing activities in accordance with established objectives. This study aimed to evaluate the reliability of the Pendekar Dewa Program implemented by PT Perusahaan Gas Negara (Persero) Tbk Pagardewa Station based on beneficiaries’ perceptions. A descriptive quantitative approach was employed using a survey method involving 52 program beneficiaries selected through incidental sampling. Data were collected through a questionnaire measuring four reliability indicators, namely the accessibility of program requirements, the conformity of program implementation with the planned schedule, the alignment of the program with its objectives, and the regularity of field facilitators in monitoring program progress. The data were analyzed using descriptive statistics to obtain mean scores and the program reliability index. The results showed that all indicators were rated in the very good category. The regularity of field facilitators in monitoring program progress achieved the highest mean score, whereas the conformity of program implementation with the planned schedule obtained the lowest score, although it remained within the very good category. Overall, the Pendekar Dewa Program achieved a reliability index score of 88.75, indicating a very good level of reliability. These findings indicate that the program is implemented consistently, aligns with its intended objectives, and is capable of meeting beneficiaries’ expectations, although scheduling aspects still require further attention to improve the quality of program implementation in the future.